2016
DOI: 10.1007/s10974-016-9460-6
|View full text |Cite
|
Sign up to set email alerts
|

L71F mutation in rat cardiac troponin T augments crossbridge recruitment and detachment dynamics against α-myosin heavy chain, but not against β-myosin heavy chain

Abstract: The N-terminal extension of human cardiac troponin T (TnT), which modulates myofilament Ca sensitivity, contains several hypertrophic cardiomyopathy (HCM)-causing mutations including S69F. However, the functional consequence of S69F mutation is unknown. The human analog of S69F in rat TnT is L71F (TnT). Because the functional consequences due to structural changes in the N-terminal extension are influenced by the type of myosin heavy chain (MHC) isoform, we hypothesized that the TnT-mediated effect would be di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…1 A), as described in the Supporting Material. We have previously shown that E D is correlated with maximal tension and that it is an approximation of the number of force-bearing XBs (24)(25)(26)(27). Two-way ANOVA of E D did not show a significant interaction effect (p ¼ 0.62), but it confirmed significant main effects of both OM (p < 0.05) and SL (p < 0.01).…”
Section: Effect Of Om On Maximal Tension and E Dmentioning
confidence: 71%
“…1 A), as described in the Supporting Material. We have previously shown that E D is correlated with maximal tension and that it is an approximation of the number of force-bearing XBs (24)(25)(26)(27). Two-way ANOVA of E D did not show a significant interaction effect (p ¼ 0.62), but it confirmed significant main effects of both OM (p < 0.05) and SL (p < 0.01).…”
Section: Effect Of Om On Maximal Tension and E Dmentioning
confidence: 71%
“…Previous studies have shown that mutations in TnT may alter the rate of XB detachment, g ( Chandra et al, 2015 ; Gollapudi and Chandra, 2016a ; Reda et al, 2016 ). Changes in SL have also been shown to impact g ( Chandra et al, 2006 ; Stelzer and Moss, 2006 ; Ford and Chandra, 2013 ), such that an increase in SL decreases g and vice versa.…”
Section: Resultsmentioning
confidence: 99%
“…S1; Ford et al, 2010). We have previously shown that tension cost and c are approximate measures of g (Campbell et al, 2004; Gollapudi et al, 2015; Reda et al, 2016). Two-way ANOVA of tension cost did not show a significant SL–MHC interaction effect (P = 0.29), but it demonstrated a significant main effect of SL (P < 0.001) and MHC (P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Such SL-mediated increase in myofilament Ca 2+ sensitivity (enhanced length-dependent activation) has been attributed to greater contribution from XB-based cooperative mechanisms that feedback to enhance thin filament Ca 2+ sensitivity (Wang and Fuchs, 1994; Fitzsimons and Moss, 1998; Smith et al, 2009). It is well documented that β-MHC XBs impart greater cooperative effects on myofilaments when compared with α-MHC XBs (Rundell et al, 2005; Ford and Chandra, 2013; Mamidi and Chandra, 2013; Michael et al, 2014; Chandra et al, 2015; Reda et al, 2016). This is presumably due to the slower cycling kinetics of β-MHC (VanBuren et al, 1995), which increases XB dwell time in the strongly bound state, thereby allowing for allosteric length-sensing mechanisms to induce greater cooperative effects on contractile function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation